Can pharmacists promote self‐care using digital technology?. Issue 2 (22nd February 2018) - Cork, Tania; Sanzeri, David; Chambers, Ruth; Chambers, Chris
Abstract : Health professionals are increasingly making use of digital technology such as healthcare apps to improve patient outcomes. Here, the authors discuss the findings of their discovery project to investigate whether community pharmacists can successfully promote patient self‐care using the Simple Florence text messaging system (Flo) and the Manage Your Health (MYH) app.